In vitro Cytotoxic Effect of Indole Alkaloids from The Roots of Kopsia singapurensis ridl. Against The Human Promyelocytic leukemia (HL-60) and The Human Cervical Cancer (HeLa) Cells - Abdul Manaf, Ali; Kartini, Ahmad; Ulil, Amna (Global Research Online, 2015)
Six indole alkaloids; kopsamine N(4)-oxide 1, kopsifine 2, rhazinicine 3, aspidodasycarpine 4, kopsamine 5 and akuammidine 6, were isolated from the roots of Kopsia singapurensis Ridl. (Apocynaceae). Compound 2 is first time isolated from the roots of K. singapurensis Ridl. Those compounds were screened for in vitro cytotoxic activity against human cervical cancer (HeLa), human promyelocytic leukemia (HL-60), and the normal mouse fibroblast (NIH/3T3) cell lines by using the MTT assay. Based on comparison with vincristine (control), kopsifine 2 showed very strong cytotoxic effects against HL-60 cells, while, kopsamine 5 exhibited a moderate cytotoxic activity effects against HL-60 cells with CD50 values of 0.9 μg/mL and 6.9 μg/mL, respectively. Akuammidine 6 and rhazinicine 3 exhibited significant cytotoxicity effects against HeLa cells with the CD50 values 2.8 μg/mL and 2.9 μg/mL, respectively. However, aspidodasycarpine 4 showed a moderate cytotoxicity effects against HeLa cells with the CD50 value of 7.5 μg/mL, and kopsamine N(4)-oxide 1 was inactive against all these cancer cells. Although kopsifine 2, rhazinicine 3, and aspidodasycarpine 4 showed high cytotoxic effects against HL-60 and HeLa cell lines, but they also showed cytotoxic on normal cell (NIH/3T3) with CD50 values of 20.7, 20.8, and 6.4 μg/mL, respectively. Therefore, these three alkaloids are not suggested as cytotoxic agents for these cancer cells. This is the first cytotoxicity report on HL-60, HeLa and NIH/3T3 cell lines for these compounds.